Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{7x+2}{5x+7}=\frac{7x-1}{5x+1}=\frac{7x+2-\left(7x-1\right)}{5x+7-\left(5x+1\right)}=\frac{7x+2-7x+1}{5x+7-5x-1}=\frac{3}{6}=\frac{1}{2}\)
tu \(\frac{7x+2}{5x+7}=\frac{1}{2}=>\left(7x+2\right).2=5x+7=>14x+4=5x+7=>14x-5x=7-4=>9x=3=>x=\frac{3}{9}=\frac{1}{3}\)
vay x=1/3
tick nha
Ta có : \(\frac{x+4}{5}=\frac{20}{x+4}\)
\(\Rightarrow\left(x+4\right).\left(x+4\right)=5.20\)
\(\Rightarrow\left(x+4\right).\left(x+4\right)=100\)
\(\Rightarrow\left(x+4\right)^2=\left(\pm10\right)^2\)
\(\Leftrightarrow\left(x+4\right)=10\)
\(\Rightarrow x=10-4\)
\(\Rightarrow x=6\)
hoặc
\(\Leftrightarrow\left(x+4\right)=-10\)
\(\Rightarrow x=-10-4\)
\(\Rightarrow x=-14\)
<=> 7 (x+9) = 2 (x+5)
<=> 7x + 63 = 2x + 10
<=> 5x = -53
<=> X=-53/5